THE NUMBER OF SPECIES OF COLLEMBOLES BY SEASONS IN THE SOIL LAYERS OF FORISH DISTRICT, JIZZAKH REGION - Atoyeva Dilsora (Journal Park Publishing, 2023)
Jizzakh region study of the number of species of collembola in light sandy soil layers of Forish district by seasons. In addition, determining the composition of the dominant species and determining the number of species by the seasonal dynamics. Collembola species are one of the indicators of stability of the earth's ecosystem in ongoing ecological processes.
Keywords: Collembola, sandy soil layers, agrocenosis, season, fauna.